PERSPEKTIF ISLAM TENTANG PENDIDIKAN MULTIKULTURAL - ., Muzakkir (Inspiratif Pendidikan, 2018)
Abstract: Allah swt. creates human beings of male and female, nation and tribe to know each other. Humans can interact well if human relations are harmoniously maintained. The perfect teaching of Islam introduces to mankind the existence of itself as an individual being as well as a social being created by Allah Almighty. which is cultured. The ability of assimilation and adaptation to fellow human beings who are of different races, ethnic, language, religion, nation, culture etc., are influenced even by one’s education. Adult guidance and direction to an immature child to recognize, understand, respect and respect others different from himself becomes a necessity in a plural society such as in the Unitary State of the Republic of Indonesia. The conscious effort of educators towards such learners is called multicultural education.